ICT and Thai Economic Growth Nexus in the Bayesian VAR Model - Rojniruttikul, Nuttawut; Vajrapatkul, Adirek (My University, 2021)
This work presents the effects of internet usage, mobile subscription, ICT export, and ICT import on Gross Domestic Product in the context of Thailand by utilizing the Bayesian vector autoregression (BVAR) model with the 24 periods of annual modified data running from 1993 to 2016. This model shows the interactions between these five variables and the forecast of GDP. The results from this work revealed that internet usage, mobile subscription, and ICT export positively affect GDP in the short run manner. Whereas ICT import showed little evidence of a negative effect on GDP. Also, this work confirms the superior forecast performance of BVER over traditional VAR. According to the results of the analysis, we hence recommend that government authorities should 1) invest or support the investments in ICT infrastructure related to internet and mobile utilization, 2) reduce the cost of acquiring internet and mobile equipment and the cost of accessing the internet and mobile service, and 3) support the ICT exporters.
Keywords: Bayesian vector autoregression; Gross Domestic Product; ICT export; ICT import; Internet usage; Mobile subscription